Math, asked by anjalighongade2510, 9 months ago

solve 12x^4-56x^3+89x^2-56x+12=0

Answers

Answered by Anonymous
2

Answer:

mark brainlist plzplzplzplz

Step-by-step explanation:

Given

12x

4

−56x

3

+89x

2

−56x+12=0 ----- (1)

on dividing equation (1) by x

2

⇒12x

2

−56x+89−

x

56

+

x

2

12

=0

12[x

2

+

x

2

1

]−56[x+

x

1

]+89=0

⇒12[(x+

x

1

)

2

−2]−56[x+

x

1

]+89=0

⇒12[x+

x

1

]

2

−56[x+

x

1

]+89−24=0

⇒12[x+

x

1

]

2

−56[x+

x

1

]+65=0

Let x+

x

1

=y

12y

2

−56y+65=0

y=

24

56+

(56)

2

−48×65

=

6

13

,

2

5

Now x+

x

1

=

6

13

or x+

x

1

=

2

5

6x

2

−13x+6=0 or 2x

2

−5x+2=0

x=

12

13±

169−144

or x=

4

25−16

x=

12

13+5

or x=

4

5+3

Hence [x=

2

3

], or [

3

2

] [x=2,

2

1

]

Answered by anushka8058
5

Answer:

14 this is right answer

Similar questions